The Influence of Financial Literacy, Mental Accounting, and Personality Traits on Financial Behavior - Pelza Yolita; Rini Indriani (CV Edujavare Publishing, 2026)
The ease of digital financial technology presents challenges for students in managing their finances, particularly due to sociocultural pressures and easy access to pay-later services. This study aims to analyze the influence of financial literacy, mental accounting, and personality traits on the financial behavior of undergraduate accounting students at the University of Bengkulu. The study used a quantitative approach with a survey method of 115 respondents selected through purposive sampling, analyzed using SPSS-based multiple linear regression. The results showed that financial literacy, mental accounting, and personality traits each had a positive and significant effect on financial behavior, contributing 55.9% to the variable. These findings confirm that financial understanding, mental budgeting skills, and personality characteristics such as accuracy and emotional stability play an important role in shaping healthy and wise financial behavior in accounting students.